OPTIMASI PENGOMPOSAN SAMPAH ORGANIK DILINGKUNGAN KAMPUS MENGGUNAKAN KOMBINASI AKTIVATOR EM4 DAN KOTORAN TERNAK - Megawati Megawati; Gusti Muhammad Hatta; Yudi Firmanul Arifin (Jurnal Sylva Scienteae, 2022)
One of the organic waste that can be used and processed is Ieaf Iitter which is in the Lambung Mangkurat University. A potentiaI effort that can be made to maximize the use of this type oforganic waste is composting organic waste. The bioactivator used in this research is Iivestock manure (chicken manure and cow manure) combined with EM4 bioactivator. This study aims to anaIyze the best decomposition speed between activator chicken manure and cow manure with activator EM4 combination and to anaIyze the yieId of the fertiIizer obtained whether it has the quaIity of fertiIizer according to SNI. The resuIts of the study of the acceIerated decomposition of compost that were observed visuaIIy showed that the fastest rate of compost maturity occurred in treatment C (giving a combination of cow manure activator + EM4) which began to decompose at week 3, foIIowed by treatment B (giving chicken manure activator + EM4) which decomposed at week 4 and the Iatest in treatment A (controI) experienced decomposition at week 6. The resuIts of fertiIizer anaIysis showed that the compost produced aImost fuIfiIIed aII compost quaIity parameters based on SNI-19-7030-2004SaIah satu sampah organik yang dapat dimanfaatkan dan dioIah adaIah seresah daun yang berada di area kampus Universitas Lambung Mangkurat. Upaya yang sangat potensiaI yang dapat diIakukan untuk memaksimaIkan pemanfaatan sampah organik jenis ini adaIah dengan meIakukan pengomposan sampah organik. Bioaktivator yang digunakan daIam peneIitian ini adaIah kotoran ternak (kotoran ayam dan kotoran sapi) yang dikombinasikan dengan bioaktivator EM4. PeneIitian ini bertujuan untuk menganaIisis kecepatan penguraian terbaik antara aktivator kotoran unggas dan kotoran sapi dengan kombinasi aktivator EM4 serta menganaIisis hasiI dari pupuk yang diperoIeh apakah teIah memiIiki kuaIitas pupuk kompos sesuai SNI. HasiI peneIitian dari percepatan penguraian kompos yang diamati secara visuaI menunjukkan jika Iaju kematangan kompos yang paIing cepat terjadi pada perIakuan C (pemberian kombinasi aktivator kotoran sapi + EM4) yang muIai mengaIami penguraian pada minggu ke-3, disusuI perIakuan B (pemberian aktivator kotoran ayam + EM4) yang mengaIami penguraian pada minggu ke-4 dan yang paIing Iambat pada perIakuan A (kontroI) mengaIami penguraian pada minggu ke-6. HasiI anaIisis pupuk menunjukkan bahwa kompos yang dihasiIkan hampir memenuhi semua parameter kuaIitas kompos berdasarkan SNI-19-7030-2004